Acute-on-Chronic Liver Failure Clinical Guidelines - Bajaj, Jasmohan S.; O'Leary, Jacqueline G.; Lai, Jennifer C.; Wong, Florence; Long, Millie D.; Wong, Robert J.; Kamath, Patrick S. (The American journal of gastroenterology, 2022)
In patients with cirrhosis and chronic liver disease, acute-on-chronic liver failure is emerging as a major cause of mortality. These guidelines indicate the preferred approach to the management of patients with acute-on-chronic liver failure and represent the official practice recommendations of the American College of Gastroenterology. The scientific evidence for these guidelines was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluation process. In instances where the evidence was not appropriate for Grading of Recommendations, Assessment, Development, and Evaluation, but there was consensus of significant clinical merit, key concept statements were developed using expert consensus. These guidelines are meant to be broadly applicable and should be viewed as the preferred, but not only, approach to clinical scenarios.